Socio-environmental risk of flooding in the basin of the Macabu River, Hydrographic Region of Baixo Paraíba do Sul and Itabapoana, Rio de Janeiro, Brazil - Vinícius Santos Lima; Rezende, Carlos Eduardo de (Geografares, 2023)
This study aimed to understand the integrated occurrence of floods and anthropogenic interventions in the Macabu River basin, focusing on their effects on land use and vegetation cover. A georeferenced multi-criteria database was created using GIS (ArcGIS 10.6.1), analyzing variables such as slope, elevation, drainage density, precipitation, and land use to generate a socio-environmental risk model for flood-prone areas, categorized into four classes: low or no risk, medium, high, and extremely high. The "high and very high" risk classes together account for 37.8% of the basin. All the mapped land uses are located in flood-prone areas, particularly non-agropastoral anthropogenic areas (78%) and non-forested natural areas (90.3%). The obtained results can inform the territorial and environmental planning of the basin, as well as areas with similar socio-environmental conditions.